Comparative analysis between the Spanish and Portuguese seismic codes. Application to a border RC primary school - Requena-García-Cruz, María-Victoria (2019)
The Iberian Peninsula is close to the Eurasia-Africa plate boundary resulting in a considerable seismic hazard. In fact, the southwestern Iberian Peninsula is affected by far away earthquakes of long-return period with large-very large magnitude. A project named PERSISTAH (Projetos de Escolas Resilientes aos SISmos no Território do Algarve e de Huelva, in Portuguese) aims to cooperatively assess the seismic vulnerability of primary schools located in the Algarve (Portugal) and Huelva (Spain). Primary schools have been selected due to the considerable amount of similar buildings and their seismic vulnerability. In Portugal, the Decreto Lei 235/83 (RSAEEP) is mandatory while in Spain, the mandatory code is the Seismic Building Code (NCSE-02). In both countries, the Eurocode-8 (EC-8) is recommended. Despite the fact that both regions would be equally affected by an earthquake, both seismic codes are significantly different. This research compares the seismic action of Ayamonte (Huelva) and Vila Real de Santo António (Portugal). Both towns are very close and located at both sides of the border. Moreover, they share the same geology. This analysis has been applied considering a RC primary school building located in Huelva. To do so, the performance-based method has been used. The seismic action and the damage levels are compared and analysed. The results have shown considerable differences in the seismic actions designation, in the performance point values and in the damage levels. The values considered in the Portuguese code are significantly more unfavourable. An agreement between codes should be made for border regions.